Cysteine cathepsins and their potential in clinical therapy and biomarker discovery. Issue 5 (24th March 2014) - Fonović, Marko; Turk, Boris; Schilling, Oliver; Findeisen, Peter
<x xml:space="preserve">Abstract</x> Since their discovery, cysteine cathepsins were generally considered to be involved mainly in the nonspecific bulk protein degradation that takes place within the lysosomes. However, it has become clear that their proteolytical activity can also influence various specific pathological processes such as cancer, arthritis, and atherosclerosis. Furthermore, their localization was found not to be limited strictly to the lysosomes. In the light of those findings, it is not surprising that cysteine cathepsins are currently considered as highly relevant clinical targets. Moreover, recent development of proteomic‐based methods for identification of novel physiological substrates of proteases provides a major opportunity also in the field of cysteine cathepsins. In this review, we will therefore present cysteine cathepsin roles in disease progression and discuss their potential relevance as prognostic and diagnostic biomarkers.